Biomolecules for nanodevice applications - Yew, Sok Yee (2009)
The density of devices needs to be integrated into various systems increases with the advancement in technology. In order to integrate high density of devices, smaller feature size down to nanometer level has to be achieved. With the current technology, copper may no longer be suitable as interconnect material due to the increase in resistance as the size of the interconnect shrinks and there is an increasing need to explore new materials with novel electron transport properties. Many work has been done on the optical interconnects and the carbon nanotube interconnects as alternatives to the conventional copper interconnects. However, both of these areas have their own limitations.